2023
DOI: 10.1101/2023.01.29.526050
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals dysregulated fibroblast subclusters in prurigo nodularis

Abstract: Prurigo nodularis (PN) is an intensely pruritic, chronic inflammatory skin disease that disproportionately affects black patients. However, the pathogenesis of PN is poorly understood. We performed single-cell transcriptomic profiling, ligand receptor analysis and cell trajectory analysis of 28,695 lesional and non-lesional PN skin cells to uncover disease-identifying cell compositions and genetic characteristics. We uncovered a dysregulated role for fibroblasts (FBs) and myofibroblasts as a key pathogenic ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
(66 reference statements)
0
8
0
1
Order By: Relevance
“…Activation of Notch signaling was observed in the lesional skin of patients with systemic sclerosis, and stimulation of healthy dermal fibroblasts with a Notch1 ligand resulted in a phenotype similar to that of systemic sclerosis with increased release of collagen and differentiation of resting fibroblasts into myofibroblasts (68). Interestingly, these findings are aligned with single-cell RNA sequencing studies indicating increased myofibroblasts in PN lesional skin (14).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Activation of Notch signaling was observed in the lesional skin of patients with systemic sclerosis, and stimulation of healthy dermal fibroblasts with a Notch1 ligand resulted in a phenotype similar to that of systemic sclerosis with increased release of collagen and differentiation of resting fibroblasts into myofibroblasts (68). Interestingly, these findings are aligned with single-cell RNA sequencing studies indicating increased myofibroblasts in PN lesional skin (14).…”
Section: Discussionmentioning
confidence: 63%
“…Periostin, an extracellular matrix protein released by skin fibroblasts, is found in the dermis of patients with PN at levels that correlate with itch intensity (74). Recent single-cell studies in PN showed significantly increased periostin in lesional skin and supports a fibroblast-neuronal axis in PN regulated by periostin (14).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…5B). A WNT5A+/POSTN+ fibroblast subset has recently been identified in the inflammatory skin disease prurigo nodularis ( 32 ). In affected individuals, these cells were shifted towards a cancer-associated phenotype and showed a prominent activation of type I interferon responses.…”
Section: Discussionmentioning
confidence: 99%
“…Damit hatte er, wie sich kürzlich herausstellte, Recht, da es sich bei der Prurigo nodularis um eine eigene Entität handelt, für die inzwischen Genotypen und Immunmechanismen beschrieben worden sind [3-7]. So wurde bei der Erkrankung anhand zellulärer und molekularer Untersuchung von Hautbiopsien eine Inflammation mit Th2-Signatur, neurofunktionelle Störungen, vermehrte Angiogenese und mesenchymale Dysregulation beschrieben [5-7]. Insbesondere die Vermehrung von Fibroblasten, Myofibroblasten und die Entstehung von Fibrose unterscheiden die Prurigo nodularis von anderen Dermatosen wie der Psoriasis und der atopischen Dermatitis.…”
unclassified